Single Phase Z-Source Inverter with Differential Evolution (DE) based Maximum Power Point Tracker - M.F.N. Tajuddin; B. Ismail; A. Azmi; S. M. Ayob; Z. Salam (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper presents an efficient power conditioning system for PV power system generation. The proposed Photovoltaic Power Conditioning System (PVPCS) used a single-stage single-phase Z-Source Inverter (ZSI) integrate with a relatively new evolutionary optimization algorithm known as the Differential Evolution (DE) as the Maximum Power Point (MPP) Tracker. Utilization of single-stage power conditioner overcomes several drawback of the two-stage configuration namely a higher part count, lower efficiency, lower reliability, higher cost and larger size. Furthermore, with a highly effective Differential Evolution (DE) based MPPT technique, the maximum power extraction from PV power generator is always at the optimum value. The proposed technique can track the true global MPP in most environmental circumstances particularly during the occurrence of partial shading condition. The proposed PVPCS is developed using MATLAB/Simulink. Simulation results show that the proposed PVPCS is able to realize inversion and boost function in single processing stage as well as dealing with partial shading condition. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7454